Orthographie im Längsschnitt. Zur Rolle schriftstruktureller Komplexität bei Wortschreibungen. - Drepper, Laura; Topalovic, Elvira (Zeitschrift für germanistische Linguistik (ZGL))
Empirical studies of the past three decades examining children’s written language acquisition suggest that students are sensitive to the acquisition of structural patterns even before the explicit teaching of orthographic phenomena. It can be assumed that structural complexity of the orthographic phenomena could be important for school acquisition processes. In the longitudinal study „Development of (Spelling) Writing from Primary to Secondary School“, the acquisition of orthographic regularities (e. g., <h> spellings, double consonance) was documented for the first time throughout the entire primary school period. In this article, we focus on word spellings, which were assessed using picture-word writing at a total of 10 time points (three assessment points in the 1st and 2nd grades and two assessment points in the 3rd and 4th grades). The subject of the analysis are the language data of children who participated in all 10 time points (n=77). The data analysis aims to answer the question of the order in which orthographic regularities are acquired. In accordance with the above-mentioned assumption, the role of the structural complexity in the acquisition order will also be examined. To this end, the results will first be examined descriptively by calculating means and standard deviations. Subsequently, inferential statistical methods for comparing means (ANOVA and t-test) will be used to test the significance of the acquisition processes. The results show that children acquire the orthographic regularities in the following order: <e> spellings in reduction syllables, syllable-initial <h> in syllabic spellings, morphological spellings in consonantal derivation, <ie> spellings in main syllables, morphological spellings in vocalic derivation, and double consonance in syllabic spellings. Furthermore, double consonance and the syllable-initial <h> are correctly realized first in syllabic and then in morphological spellings. Based on the results, the importance of structural complexity for spelling acquisition, for example with regard to syllabic and morphological spellings, as well as the implications of the results for teaching practice are discussed.

Mehrebenenannotation argumentativer Lerner*innentexte für die automatische Textauswertung - Rezat, Sara; Kilsbach, Sebastian; Michel, Nadine; Karabey, Rabia; Stahl, Maja; Wachsmuth, Henning (Zeitschrift für Angewandte Linguistik)

AnnoPy. Ein digitales Tool zur Förderung von Textkompetenzen - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)
Im Beitrag wird ein digitales Tool zur fächerübergreifenden Förderung von Textkompetenzen vorgestellt. Zunächst werden die Funktionen des Tools beschrieben und das zugrundeliegende tool-based task Design erläutert. Anhand eines Lehr-Lern-Arrangements zum argumentierenden Schreiben wird exemplarisch gezeigt, wie das Tool im Deutschunterricht eingesetzt werden kann. Anschließend werden erste empirische Befunde aus der am Design-Based-Research orientierten Studie vorgestellt. Abstract (english): AnnoPy – A digital tool for cross-curricular text literacy development In this article we present a digital tool for cross-curricular text literacy development. At first, we describe the basic functions of the tool and the underlying tool-based task design. After that, a teaching arrangement for German lessons is used to show how the tool can be used to foster argumentative writing. Subsequently, first results of the design-based study are presented.
Keywords: Textkompetenz; Digitales Lesen und Schreiben; Kollaborativer Umgang mit Texten; Prozedurenorientierte Schreibdidaktik; Design-based-Research

Lerngegenstand „Doppelkonsonanz“ in der Grundschule: Explizites und implizites Lernen im Längsschnitt. - Topalović, Elvira; Drepper, Laura; Härtel, Kira (Lesen- und Schreibenlernen im Spannungsfeld zwischen Wissen und Können)

Sprachliche Bildung - Topalović, Elvira; Settinieri, Julia

Fridolin-Duck Karotti. Mit einem kollaborativen Schreibtool gemeinsam Fantasiere beschreiben - Rezat, Sara; Scholle, Oliver; Bendner, Sarah (Praxis Deutsch 292)

Digital lesen und schreiben. Basisbeitrag - Rezat, Sara (Praxis Deutsch)

Fridolin-Duck Karotti. Mit einem kollaborativem Schreibtool gemeinsam Fantasietiere beschreiben - Rezat, Sara; Scholle, Oliver (Praxis Deutsch)

Lesen und Schreiben: digital. Praxis Deutsch 292

Texte im Deutschunterricht. - Rezat, Sara (12 Perspektiven auf den Deutschunterricht. Wissenswertes für Deutschlehrkräfte.)

Schreiben - Rezat, Sara (Basiswissen Lehrerbildung: Deutsch unterrichten)

Das Stellungsfeldermodell im Deutschunterricht: Wie urteilen Lehrkräfte über ein grammatisches Modell? - Topalović, Elvira; Uhl, Benjamin (Grammatische Modellierung als Grundlage für sprachdidaktische Vermittlung. Linguistische Berichte (LB))

Wirklichkeit(en) konstruieren: Die Mediendidaktik Deutsch als Säule oder Fundament? - Topalović, Elvira (Didaktik Deutsch)

Erklärtexte lesen und schreiben. Praxis Deutsch 285

Zur makrostrukturellen Prägung argumentierender Textprozeduren - Rezat, Sara (ar|gu|men|tie|ren. Eine zentrale Sprachhandlung im Fach- und Sprachunterricht)

Digitale Desinformation und Fake News. Schülerinnen und Schüler erklären, warum Fake News sich so gut verbreiten - Rezat, Sara; Arnold, Cynthia (Praxis Deutsch 285)

Erklärtexte lesen und schreiben. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 285)

In Krisen erzählen – von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Mehrdeutigkeiten
Keywords: General Earth and Planetary Sciences; General Environmental Science

Komplexe Wörter richtig schreiben. Wortanalyse als Rechtschreibstrategie. - Lang, Susanne; Topalović, Elvira (In: Praxis Deutschunterricht)